Contemporary Ideas on Ship Stability Risk of Capsizing - Belenky, Vadim L.; Spyrou, Kostas J.; van Walree, Frans; Almeida Santos Neves, Marcelo; Umeda, Naoya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book contains a selection of research papers presented at the 11th and 12th International Ship Stability Workshops (Wageningen, 2010 and Washington DC, 2011) and the 11th International Conference on Stability of Ships and Ocean Vehicles (Athens, 2012). The book is directed toward the ship stability community and presents innovative ideas concerning the understanding of the physical nature of stability failures and methodologies for assessing ship stability. Particular interest of the readership is expected in relation with appearance of new and unconventional types of ships; assessment of stability of these ships cannot rely on the existing experience and has to be based on the first principles. As the complexity of the physical processes responsible for stability failure have increasingly made time-domain numerical simulation the main tool for stability assessment, particular emphasis is made on the development an application of such tools. The included papers have been selected by the editorial committee and have gone through an additional review process, with at least two reviewers allocated for each. Many of the papers have been significantly updated or expanded from their original version, in order to best reflect the state of knowledge concerning stability at the time of the book's publication. The book consist of four parts: Mathematical Model of Ship Motions in Waves, Dynamics of Large Motions, Experimental Research and Requirements, Regulations and Operations.
Preface -- Introductory Note -- Part A: Mathematical Model of Ship Motions in Waves -- A1 New Simulation Tools -- A1.1 TEMPEST: A New Computationally Efficient Dynamic Stability Prediction Tool, by W.F. Bellknap and A.M. Reed -- A2 Wave Enviroment -- A2.1 Modeling of Incident Waves near the Ship's Hull (Application of Autoregressive Approach in Problems of Simulation of Rough Seas), by A. B. Degtyarev and A.M. Reed -- A2.2 Evaluation of hydrodynamic pressures for autoregression model of irregular waves, by A.B. Degtyarev and I. Gankevich -- A3 Consideration of Forces -- A3.1 Application of computing hydrodynamic forces and moments on a vessel without Bernoulli's equation, by A. M. Reed -- A3.2 Modelling of Hull Lift and Cross Flow Drag Forces in Large Waves in a Computationally Efficient Dynamic Stability Prediction Tool, by M. J. Hughes, P. J. Kopp and R. W Miller -- A3.3 Improved Maneuvering-Based Mathematical Model for Free-Running Ship Motions in Following Waves using High-Fidelity CFD Results and System-Identification Technique, by M. Araki, H. Sadat-Hosseini, Y. Sanada, N. Umeda, F. Stern -- A4 Roll Damping -- A4.1 Some Results from a New Time-Domain Bilge Keel Force Model, by D. S. Greeley -- A4.2 Some Topics for Estimation of Bilge Keel Component of Roll Damping, by T. Katayama, Y. Yoshioka, T. Kakinoki and S. Miyamoto -- A4.3 Considerations for Bilge Keel Force Models in Potential Flow Simulations of Ship Maneuvering in Waves, by C. Bassler, R. Miller, A. M. Reed and A. Brown -- A4.4 Assessment of ship roll damping through full scale and model scale experiments and semi-empirical methods, by C.-J. Soder, A. Rosen, S. Werner, M. Huss and J. Kuttenkeuler -- A4.5 Roll damping of twin-screw vessels: comparison of RANSE with established methods, by S. Handschel, N. Kollisch and M. Abdel Maksoud -- A5.1 Calculation method to include water on deck effects, by N. Carette and F. van Walree -- A5.2 Study on the motions and flooding process of a damaged ship in waves, by S.-K. Cho, H.-G. Sung, S-Y. Hong, B.-W. Nam and Y.-S. Kim -- A5.3 Numerical Study of Damaged Ship Motion in Waves, by Z. Gao, Q. Gao and D. Vassalos -- A5.4 3D GPU SPH analysis of coupled sloshing and roll motion, by L. Perez Rojas and J.L. Cercos Pita -- Part B. Dynamics of large motions -- B1 Parametric Roll -- B1.1 Prediction of Parametric Rolling in Irregular Head Waves, by H. Hashimoto, N. Umeda and Y. Sogawa -- B1.2 Investigation on parametrically excited motions of Spar platforms in waves, by C. A. Rodriguez and M. A. S. Neves -- B1.3 A study on unstable motions of a tension leg platform in close proximity to a large FPSO, by L. A. Rivera, M. A. S. Neves, R. E. Cruz and P. T. T. Esperanca -- B2 Surf-riding -- B2.1 Continuation analysis of surf-riding and periodic responses of a ship in steep quartering seas, by I. G. Tigkas and K. J. Spyrou -- B2.2 Evaluation of the probability of surf-riding in irregular waves with the time-split method, by V. Belenky, K. J.Spyrou and K. M. Weems -- B2.3 Definitions of Celerity for Investigating Surf-riding in An Irregular Seaway, by K. J. Spyrou, V. Belenky, N. Themelis and K. M. Weems -- B3 Stochastic Dynamics -- B3.1 Estimating Dynamic Stability Event Probabilities from Simulation and Wave Modeling Methods, by M. R. Leadbetter, I. Rychlik and K. Stambaugh -- B3.2 Stochastic Wave Inputs for Extreme Roll in Near Head Seas, by D. H. Kim and A. W. Troesch -- B3.3 Critical wave groups vs. direct Monte-Carlo simulations for typical stability failure modes of a container ship, by V. Shigunov, N. Themelis and K. J. Spyrou -- B3.4 Application of stochastic dynamical system to nonlinear ship rolling problems, by J. Falzarano, Z. Su and A. Jamnongpipatkul -- B3.5 The Capsize Band Concept Revisited, by N. Tsakalakis, J.Cichowisz and D.Vassalos -- B3.6 Dependence of roll and roll rate in nonlinear ship motions in following and stern quartering seas, by V. Belenky and K. M. Weems -- C. Experimental research -- C1Experimemintal Techniques -- C1.1 Regular Wave Testing as a Crucial First Step for Dynamic Stability Evaluation, by D. D. Hayden, R. C. Bishop, and M. J. Dipper -- C1.2 An experimental study on characteristics of rolling in head waves for a vessel with non-linear GZ-curve, by T. Katayama, S. Miyamoto, H. Hashimoto and Y. Tai -- C1.3 Experimental Ship Dynamic Stability Assessment Using Wave Groups, by C. C. Bassler, M. J. Dipper, Jr. and M. Melendez -- C1.4 Dynamic transverse stability for high speed craft, by C. Q. Judge -- C1.5 Experiments on a Floating Body Subjected to Forced Oscillation in Calm Water at the Presence of an Open-to-Sea Compartment, by J. Chichowicz, D. Vassalos and A. Jasionowski -- C2 Validation and Benchmarking -- C2.1 Model characteristics and validation approach for a simulation tool supporting direct stability assessment, by W. F. Belknap, A. M. Reed and M. J. Hughes -- C2.2 Validation Approach for Statistical Extrapolation, by T.C. Smith -- C2.3 Total stability failure probability of a ship in beam wind and waves: model experiment and numerical simulation, by T. Kubo, N. Umeda, S. Izawa and A. Matsuda -- C2.4 Deterministic Validation of a Time Domain Panel Code for Parametric Roll, by F. van Walree and P. de Jong -- C2.5 26th ITTC Parametric Roll Benchmark Study, by A. M. Reed -- C2.6 An Approach to the Validation of Ship Flooding Simulation Models, by E. Ypma and T. Turner -- D. Requirements, regulations and operation -- D1 Developments in Intact Stability Regulations -- D1.1 Research towards Goal Based Standards for Container Shipping, by V. Shigunov, H. Rathje and O. El Moctar -- D1.2 On regulatory framework for direct stability assessment, by W. S. Peters, V. Belenky and A. M. Reed -- D1.3 A probabilistic analysis of stability regulations for river-sea ships, by I. Backalov -- D2 Developments in Damage Stability Regulations -- D2.1 Issues Related to Damage Stability, by A.L. Scott -- D2.2 Damage Stability Making Sense, by D. Vassalos -- D2.3 Coupling of progressive structural failure and loss of stability in the safe return to port framework , by S. Kwon, Q. Chen, G. Mermiris and D. Vassalos -- D2.4 Impact of Watertight Door Regulations on Ship Survivability, by J. PersonD2.5 Damage stability of passenger ships - notions and truths, by D. Vassalos -- D2.6 Defining Rational Damage Stability Requirements, by N. Tsakalakis, D. Konovessis and D. Vassalos -- D3 Stability Requirements in Operation -- D3.1 Design requirements for stability and minimal motions in a storm, by V. N. Khramushin -- D3.2 Further Perspectives on Operator Guidance and Training for Heavy Weather Ship Handling, by L.J. Van Buskirk, J.McTigue and P.A. Alman -- D3.3 Onboard Analysis of Ship Stability Based on Time-Varying Autoregressive Modeling Procedure, by D. Terada and A. Matsuda -- D3.4 FLO/FLO Heavy lift critical stability phases, by P. Handler, V. Jarecki and H. Bruhns -- D4 Stability of Naval Vessles -- D4.1 Developing a Shared Vision for Naval Stability Assessment, by D. Perrault. T. Hughes and S. Marshall -- D4.2 Approaches for Evaluating Dynamic Stability in Design, by P.R. Alman -- D4.3 Tolerable Capsize Risk of a Naval Vessel, by A. Peters -- D4.4 Thoughts on Integrating Stability into Risk Based Methods for Naval Ship Design, by P. R. Alman -- Author Index -- Subject Index.
Keywords: Offshore structures; Continuum mechanics; Fluid mechanics; Offshore Engineering; Continuum Mechanics; Engineering Fluid Dynamics